Crime and police resources: the street crime initiative - Machin, Stephen (2005)
In this paper we look at links between police resources and crime in a different way to the existing economics of crime work. To do so we focus on a policy intervention - the Street Crime Initiative - that was introduced in England and Wales in 2002. This allocated additional resources to some police force areas to combat street crime, whereas other forces did not receive any additional funding. Estimates derived from several empirical strategies show that robberies did fall significantly in SCI police forces relative to non-SCI forces after the initiative was introduced. Moreover, the policy seems to have been a cost effective one. There is some heterogeneity in this positive net social benefit across different SCI police forces, suggesting that some police forces may have made better use of the extra resources than others. Overall, we reach the conclusion that increased police resources do in fact lead to lower crime, at least in the context of the SCI programme we study